Penyusunan Perencanaan Pembangunan Pada Badan Perencanaan Pembangunan Daerah Kabupaten Bangli - Ni Made Heryani Dian Indraswari; I Wayan Sudemen; Nyoman Sumawidayani (Policy and Maritime Review, 2024)
The Planning Agency of Bangli Regency plays a role in formulating development plans to realize the New Era of Bangli. However, this institution faces obstacles in the form of limited human resources and insufficient regional funds, which hinder the planning process. Therefore, this study aims to review and analyze human resource performance and budgeting as important factors in supporting the achievement of the New Era of Bangli. This study uses a type of qualitative research using data analysis techniques, namely Data Collection, Data Reduction, Data Display, Conclussion Drawing/Verifying which connects events and describes phenomena in the field that are the topic of research through observation, interviews, and documentation and uses organizational performance theory from Kumorotomo with 4 indicators, namely Efficiency, Effectiveness, Fairness, and Responsiveness. The results of the study show that Human Resources (HR) in the Regional Development Planning Agency cannot be fully said to be in accordance with the Efficiency and Effectiveness indicators because of the inhibition in the development planning process due to the delay in SIPD verification and lack of training in planning. Meanwhile, budgeting has been said to be running quite well because of the allocation of funds used according to needs in the formulation of programs and activities.